IMPROVING STUDENTS' ABILITY IN READING EXPOSITORY TEXTS USING DIRECTED READING-THINKING ACTIVITY (DRTA) STRATEGY - IKA PUSPITARINI; SANTI ERLIANA; NOVI SRIWULANDARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
Critical thinking can be considered as the ultimate goal in the process of teaching and learning. It is an organized process that needs highly order of mental activities, such as analyzing, associating, distinguishing, interpreting, and summarizing the information in order not to Ã¢â‚¬Å“createÃ¢â‚¬Â bias in every decision made. Teachers have a paramount task to help the students to develop their critical thinking. One way to build this critical thinking is through reading, introducing one of reading strategies, named Directed Thinking Reading Activity (DR-TA). DRTA extends reading to higher-order thought processes and provides lecturers with a great deal about each student's ideas, thought processes, prior knowledge and thinking skills. DR-TA also contains of activities that encourages critical awareness of the readerÃ¢â‚¬â„¢s role and active involvement with text through the process of predicting, verifying, judging, and extending thinking about the text material. Hence, it can be promoted to be one of ways to build the critical thinking among the students.